Parietal wall endometriosis: a rare case report - Sahu, Mahija; Ray, Umesh; Nayak, Bhabani Sankar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A 28 year old P2L1 with one previous cesarean presented with cyclical pain in periumblical area just below umbilicus for 1 year with USG finding suggestive of parietal wall endometriosis planned for surgery on her 2nd day of menstruation. She underwent diagnostic laparoscopy with complete excision of endometrioma. Diagnostic laparoscopy showed no evidence of endometrioma in the pelvic cavity except for omental adhesion at parietal wall endometrioma site, adhesiolysis of omentum, mesh repair of rectus sheath defect done. She is followed up for last 3 cycles post-operative and has no cyclical pain further.